Receding horizon control of switching systems - Lee, Y; Kouvaritakis, B; IEEE (2006)
This paper provides a receding horizon control method for discrete-time switching systems. Switching systems are assumed to be represented by different linear state space models; one for each switching state of the switching components. The concept of periodic invariance can be applied to this converter system in such a way that a set is periodic invariant with respect to a switching sequence if it is possible to ensure that all the states are returned back into the set when the system dynamics is switched according to the components' switching sequence. The periodic use of the switching sequence could be used to guarantee the stability of the circuit, and performance can be enhanced by receding horizon application of the switching sequence. Simulation results show that the proposed method yields good performance for an up-down power converter. © 2006 IEEE.